Integrating immersive technologies with STEM education: a systematic review - Tene, Talia; Marcatoma Tixi, Jessica Alexandra; Palacios Robalino, María de Lourdes; Mendoza Salazar, María José; Vacacela Gomez, Cristian; Bellucci, Stefano (Frontiers in Education, 2024)
Objective: This systematic review aims to synthesize current knowledge on integrating immersive technologies, namely Virtual Reality (VR) and Augmented Reality (AR), in STEM (Science, Technology, Engineering, Mathematics) education, and to lighten their impact on student performance and engagement. Methods: Adhering to PRISMA guidelines, a detailed search strategy across Scopus and Web of Science databases identified relevant peer-reviewed journal articles published from 2002 to 2023. The PICOS approach informed our inclusion criteria, focusing on empirical studies that assessed the application of VR and AR technologies in STEM (Science, Technology, Engineering, Mathematics) educational settings. Studies were evaluated for methodological quality, and data extraction was meticulous, with variables categorized as engagement, performance, or a combination of both. Analysis: A descriptive and statistical analysis using chi-square tests was employed to examine the relationship between the type of technology (AR, VR, XR, MR) and the educational outcomes. This quantitative assessment provided a nuanced understanding of the interplay between various immersive technologies and their pedagogical effectiveness. Results: Out of 143 initially identified articles, 22 met the inclusion criteria for detailed analysis. Findings revealed that AR was the most studied technology, followed by VR. Most studies reported positive effects on student engagement and performance, with increased effectiveness being less frequently observed. A notable portion of the studies specifically investigated the combination of performance and engagement, underscoring the multifaceted benefits of immersive technologies in education.Conclusions: Immersive technologies are reshaping STEM education by enhancing engagement and performance. Integrating VR and AR offers promising educational benefits, including improved comprehension of complex concepts, increased student motivation, and enriched collaborative learning experiences. However, the field requires a globally inclusive and adaptable framework for rapid technological evolution and diverse educational contexts.Future research should broaden its scope to include multilingual literature and non-traditional academic channels, ensure ethical standards are upheld, and focus on personalization and adaptability to maximize the educational potential of these technologies.